YAP promotes proliferation, chemoresistance, and angiogenesis in human cholangiocarcinoma through TEAD transcription factors - Marti, Patricia; Stein, Claudia; Blumer, Tanja; Abraham, Yann; Dill, Michael T.; Pikiolek, Monika; Orsini, Vanessa; Jurisic, Giorgia; Megel, Philippe; Makowska, Zuzanna; Agarinis, Claudia; Tornillo, Luigi; et al. (Hepatology (Baltimore, Md.), 2015)
The Yes‐associated protein (YAP)/Hippo pathway has been implicated in tissue development, regeneration, and tumorigenesis. However, its role in cholangiocarcinoma (CC) is not established. We show that YAP activation is a common feature in CC patient biopsies and human CC cell lines. Using microarray expression profiling of CC cells with overexpressed or down‐regulated YAP, we show that YAP regulates genes involved in proliferation, apoptosis, and angiogenesis. YAP activity promotes CC growth in vitro and in vivo by functionally interacting with TEAD transcription factors (TEADs). YAP activity together with TEADs prevents apoptosis induced by cytotoxic drugs, whereas YAP knockdown sensitizes CC cells to drug‐induced apoptosis. We further show that the proangiogenic microfibrillar‐associated protein 5 (MFAP5) is a direct transcriptional target of YAP/TEAD in CC cells and that secreted MFAP5 promotes tube formation of human microvascular endothelial cells. High YAP activity in human CC xenografts and clinical samples correlates with increased MFAP5 expression and CD31+ vasculature. Conclusions: These findings establish YAP as a key regulator of proliferation and antiapoptotic mechanisms in CC and provide first evidence that YAP promotes angiogenesis by regulating the expression of secreted proangiogenic proteins. (Hepatology 2015;62:1497–1510)